Association of transcallosal motor fibres with function of both hands after unilateral neonatal arterial ischemic stroke. (17th August 2017) - Groeschel, Samuel; Hertz‐Pannier, Lucie; Delion, Matthieu; Loustau, Sébastien; Husson, Béatrice; Kossorotoff, Manoelle; Renaud, Cyrille; Nguyen The Tich, Sylvie; Chabrier, Stéphane; Dinomais, Mickael; ,
Abstract : Aim: The objective of this study was to investigate the involvement of the motor fibres of the corpus callosum after unilateral neonatal arterial ischemic stroke (NAIS) of the middle cerebral artery territory and the relationship to both ipsilesional and contralesional hand function. Method: Using high‐resolution structural magnetic resonance imaging (MRI), functional MRI, and magnetic resonance diffusion‐tractography, we compared the midsagittal area of the motor part of the corpus callosum (defined by the fibres connecting the precentral gyri) between 33 7‐year‐old children after unilateral NAIS and 31 typically developing 7‐year‐old children. Hand motor performance was assessed by the box and blocks test. Results: Children after NAIS showed on average significantly smaller motor corpus callosum area compared to typically developing children ( p <0.001, without differences of the non‐motor corpus callosum area). In addition, there was a significant positive association between the motor part of the corpus callosum and both contralesional (Pr(>| t |)=0.034) and ipsilesional hand motor performance (Pr(>| t |)=0.006) after controlling for lesion volume and sex. In a post‐hoc analysis the additional contribution of corticospinal tract damage was evaluated. Interpretation: Compared to typically developing children, children after NAIS exhibited a smaller motor part of their corpus callosum associated with reduced contralesional but also ipsilesional manual dexterity. These results indicate that the affection of transcallosal motor fibres in unilateral NAIS might be of functional relevance and an important part of the involved structural network that should be elucidated in further studies. What this paper adds: Unilateral neonatal arterial ischemic stroke (NAIS) in middle cerebral artery territory affects transcallosal motor fibres. Affection of transcallosal motor fibres after NAIS is associated with both contralesional and ipsilesional gross manual dexterity as assessed by box and block test. Unilateral lesions in the developing brain may influence dexterity of both hands through involvement of corpus callosum. This article is commented on by Bekiesińska‐Figatowska on pages992–993 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.